Sistem Informasi Point Of Sale (POS) Berbasis Web Menggunakan Metode Prototype Pada Toko Kasse - Mico Giovanni Dermawan; Suherman Suherman; Wahyu Hadikristanto (DPPM Universitas Pelita Bangsa, 2022)
In the age of computerized technology in small or medium-scale goods trading companies in Indonesia, there are still many who have not used it. Like the Kasse Store, it still doesn’t use computer technology. There are still use the manual method of collecting transaction data, because they still use the book system to record sales transaction. This Point of Sale application will be designed using the prototyping method and also using PHP and MySQLi because it saves time. The goal is for Kasse Store to be able to collect all sales transaction data without having to hardwrite it in a book. The result of this research is a web-based Point of Sale application that can document and produce detailed reports, making activities easier and more efficient. The conclusion is with the Point of Sale application at the Kasse Store can save time in making sales transaction and as an automatioc income counter. Keywords: Point of Sale Application, Prototyping Method, PHP, MySQLi